Understanding Globalization, Global Gaps, and Power Shifts in the 21st Century CCG Global Dialogues - Wang, Huiyao; Miao, Lu (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book aims to help readers make sense of our changing world by sharing the views of global thought leaders on some of the most important issues of our time, from US-China relations and global governance to climate change and the COVID-19 pandemic. The ten dialogues in this book were part of the "China and the World" series of online discussions hosted by the Center for China and Globalization (CCG). The series features CCG President Huiyao Wang in conversation with experts from a range of fields, from renowned scholars of international relations, economics, and history, to journalists, policymakers, and business leaders. The speakers featured in this book are Graham Allison, David Blair, Kerry Brown, Anne Case, Li Chen, Wendy Cutler, Angus Deaton, Thomas L. Friedman, Valerie Hansen, Pascal Lamy, Kishore Mahbubani, Joseph S. Nye Jr., Adam Posen, J. Stapleton Roy, John L. Thornton, Huiyao Wang, Martin Wolf, and Zhu Guangyao. These wide-ranging discussions offer unique insights and perspectives on key trends shaping our world in the 21st century. These include the rise of China and shifts in geopolitics, as well as the evolving nature of globalization, transnational threats, and multilateralism. Huiyao Wang is the founder and President of CCG, a former Counselor of the State Council of China and Dean of the Institute of Development Studies of Southwestern University of Finance and Economics of China. Lu Miao is Secretary-General of CCG, a Young Leader for Munich Security Conference Young Leader(MSC), and the Deputy Director-General of the International Writing Center of Beijing Normal University.